Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/1479972314562209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical insufflation/exsufflation improves vital capacity in neuromuscular disorders

Abstract: Inherited neuromuscular disorders inevitably result in severe lung volume restriction associated with high morbidity and mortality. The aim of this retrospective study was to evaluate the long-term effects of the regular use of mechanical insufflation/exsufflation on the course of the vital capacity. This retrospective data analysis included 21 patients (16.1 + 6.5 years) with neuromuscular disorders and severe lung volume restriction using nocturnal noninvasive ventilation. The patients were advised to regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
1
31
0
3
Order By: Relevance
“…Our observed maximum decline in VC occurring between ages 20 and 21 years can also be compared to the maximum annual rate of decline of 39% and median 8%/year over multiple years reported by Wagner et al for untreated patients (23) and to decreases of 8.5-14%/year over multiple years reported in other studies that identified neither maximum rates of VC decline nor plateau VC (15,16,18,(24)(25)(26)(27)(28)(29). These studies reported decreases in the percentage of predicted VC over ages 10-20 years, of 8.5%/year, or 85% over 10 years (3), 5%/year over ages 5-24 years (n = 60) (26), 8%/year over ages 10-18 years (n = 58) (27,30,31); 10.7%/year over ages 12-15 years (n = 10) (28), and 4.2%/year at mean age 13 years (n = 25) (16).…”
Section: Discussionsupporting
confidence: 82%
“…Our observed maximum decline in VC occurring between ages 20 and 21 years can also be compared to the maximum annual rate of decline of 39% and median 8%/year over multiple years reported by Wagner et al for untreated patients (23) and to decreases of 8.5-14%/year over multiple years reported in other studies that identified neither maximum rates of VC decline nor plateau VC (15,16,18,(24)(25)(26)(27)(28)(29). These studies reported decreases in the percentage of predicted VC over ages 10-20 years, of 8.5%/year, or 85% over 10 years (3), 5%/year over ages 5-24 years (n = 60) (26), 8%/year over ages 10-18 years (n = 58) (27,30,31); 10.7%/year over ages 12-15 years (n = 10) (28), and 4.2%/year at mean age 13 years (n = 25) (16).…”
Section: Discussionsupporting
confidence: 82%
“…McKim et al also reported retrospectively an 89% decrease in VC decline over a period of 78 months follow-up in 22 DMD patients who were prescribed lung volume recruitment sessions [130]. In another retrospective study on a mixed population of 21 patients with NMDs, the regular use of the MI-E device resulted in improvement in VC by 28% during the first year and stabilization during the second year [131].…”
Section: Respiratory Management Of Patients With Neuromuscular Diseasesmentioning
confidence: 93%
“…Conversely, a 3‐month, matched‐pair randomized controlled trial (RCT) of inflations in children with DMD found no difference in FVC between those treated with daily IPPB compared to control . Dosage was different between the studies and may explain some of the variability; inflation pressures ranged from 18 to 40 cm H 2 O compared to 10–18 cm H 2 O, and treatment time was 20 versus 6 min per day.…”
Section: Evidence Of Efficacy During Clinical Stabilitymentioning
confidence: 99%
“…retrospectively analysed the records of 21 patients with heterogeneous NMD advised to perform b.d. MI‐E incorporating inflations and found an increase in VC in 86% of patients within the first year . Conversely, a 3‐month, matched‐pair randomized controlled trial (RCT) of inflations in children with DMD found no difference in FVC between those treated with daily IPPB compared to control .…”
Section: Evidence Of Efficacy During Clinical Stabilitymentioning
confidence: 99%